Knowledge Sharing, Work Ethics and Auditors’ Innovation Capability: A Comparative Study in Malaysia and Indonesia - Abd-Mutalib, Hafizah; Oktaroza, Magnaz Lestira; Jamil, Che Zuriana Muhammad; Maemunah, Mey (CENTRAL ASIA AND THE CAUCASUS, 2024)
The tremendous development in technology has put auditors in a challenging situation to perform their audit which requires tracking vast amounts of data, often in a paperless environment. Therefore, auditors need to be innovative in performing audits in order to stay relevant. The objective of this study is to examine innovation capability of external auditors when performing audits. This study specifically examines if knowledge sharing (proxied by knowledge collecting and knowledge donating) and work ethics, contribute to auditors’ innovation capability in Malaysia and Indonesia. The results reveal that auditors in both countries perceive that they can be innovative; Malaysian auditors show slightly higher capability compared to their Indonesian counterparts. Furthermore, knowledge donating positively influences auditors’ innovation capability in both countries, while knowledge collecting positively influences only Indonesian auditors’ innovation capability. This may be due to the high usage of Information and Communications Technology (ICT) in Malaysian audit firms, which generates a greater flow of codified knowledge, whilst inhibiting the less formal or simple method of sharing information, such as by using knowledge collecting. Meanwhile, the positive impact of work ethics is only found in the Malaysian setting.